Consolidation of primary care physicians and its impact on healthcare utilization. (25th March 2021) - Zhang, Jonathan; Chen, Yiwei; Einav, Liran; Levin, Jonathan; Bhattacharya, Jay
Abstract: We use administrative data from Medicare to document the massive consolidation of primary care physicians over the last decade and its impact on patient healthcare utilization. We first document that primary care organizations have consolidated all over the United States between 2008 and 2014. We then show that regions that experienced greater consolidation are associated with greater decline in overall healthcare spending. Finally, in our primary exercise, we exploit transitions of patients across organizations that are driven by changes in the organizational affiliations of their primary care physicians to study the impact of organizational size on overall spending. Our preferred specification suggests that patients switching from small to large physician organizations reduce their overall healthcare spending by 16%, and that this reduction is primarily driven by a 13% reduction in primary care visits and 0.09 (21%) fewer inpatient admissions per year.